2020
DOI: 10.1002/eat.23258
|View full text |Cite
|
Sign up to set email alerts
|

Peer mentorship as an adjunct intervention for the treatment of eating disorders: A pilot randomized trial

Abstract: Objective: Peer mentorship has been shown to be helpful for other mental health conditions, but it has been understudied for patients with eating disorders. The goal of the present study was to evaluate the feasibility and efficacy of peer mentorship for individuals with eating disorders by conducting a randomized controlled trial (RCT).Trial Design: Parallel three-arm pilot RCT with 1:1:1 allocation to peer mentorship, social support mentorship (active comparison intervention), and waiting list.Method: Sixty … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
40
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 33 publications
(48 citation statements)
references
References 30 publications
0
40
0
Order By: Relevance
“…Thus digital systems are of promise in a variety of forms to augment treatment such as virtual reality to target food or body image fears and training approaches to improve food and social approach behaviours. Also given the long course of the illness, a recovery approach with peer support may enhance hope (Ranzenhofer et al, 2020). Social support provided from family, friends and people with lived experience in connection with a consultative and tailored service approach might allow a more optimised, personalised approach to care (Treasure, Willmott, et al, 2020).…”
Section: New Treatmentsmentioning
confidence: 99%
“…Thus digital systems are of promise in a variety of forms to augment treatment such as virtual reality to target food or body image fears and training approaches to improve food and social approach behaviours. Also given the long course of the illness, a recovery approach with peer support may enhance hope (Ranzenhofer et al, 2020). Social support provided from family, friends and people with lived experience in connection with a consultative and tailored service approach might allow a more optimised, personalised approach to care (Treasure, Willmott, et al, 2020).…”
Section: New Treatmentsmentioning
confidence: 99%
“…There is some indication that peer mentorship can help patients feeling understood and improve clinical outcomes and treatment attendance (Beveridge et al, 2019 ; Perez, Van Diest, & Cutts, 2014 ; Ramjan, Fogarty, Nicholls, & Hay, 2018 ). A recent pilot randomized controlled trial (RCT) examining the feasibility and efficacy of peer mentorship for individuals with an eating disorder found a preference for, and higher engagement with peer mentors, compared to general social support mentorship (Ranzenhofer et al, 2020 ).…”
Section: Introductionmentioning
confidence: 99%
“…Peer support appears useful in modelling the recovery journey and providing hope (Cardi et al, 2015). A recent pilot RCT with eating disorder patients who had been discharged from a higher level of care, reported that peer mentorship provided by people with lived experience of an eating disorder resulted in greater symptom reduction and higher attendance and acceptability ratings, compared to social support mentorship (by individuals without lived experience) or waiting list controls (Ranzenhofer et al, 2020).…”
Section: Discussionmentioning
confidence: 99%